STATUS AND TRENDS OF MONITORING INSECT POLLINATORS IN MANGO ECOSYSTEM IN SOUTHERN GHANA - Annoh, Charles. E.; A. Ewusie, Ebenezer.; A. Cobblah, Millicent.; Y. Osae, Michael.; A. Boateng, Bernard.; Kwapong, Peter. K.; Aidoo, Kwame.; Bosu, Paul. P. (IJRDO-Journal of Applied Science, 2017)
Several insects including the bees and other animals like bats are estimated to boost pollination services of 35% of the world’s food crops like mangoes, vegetables and medicinal plants. Researchers have shown declining trends of populations of some wild pollinators, particularly the honey bee. This study was to determine insect diversity, abundance and monitor seasonal trends of insect pollinators in the mango ecosystem of ten selected farms in the southern part of Ghana. In each farm, a radial transect of 10-meter diameter was constructed. Thirty small plastic pan traps were placed singly on 30 polyvinylchloride pipes fixed at 1-meter intervals. The pan traps filled with soapy water, were colored of ten cohorts of florescent blue, yellow and white respectively. Monitoring was conducted during the flowering periods of the minor and major mango seasons of 2012 and 2013. A total of 2364 insects were trapped; the most abundant were dipterans (1435) largely made up of house flies. The hymenopterans (504) consisted of 418 bees and 86 wasps respectively. Blue (2.85) and white (2.09) colored traps attracted bees more than yellow (1.62) colored traps (p=0.89). The flies were most attracted to white traps (5.38) followed by yellow (4.35) and blue (3.61), the least (p=1.35). In farms close to natural vegetation bees declined from 3.00 per trap per week in 2012 major season through to 1.00 in 2013 major season. The declining trend of bees in this study underscores the need to manage and conserve wild pollinators for sustainable food productivity